1995
DOI: 10.1071/ea9950997
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage, stubble, gypsum, and nitrogen fertiliser on cereal cropping on a red-brown earth in south-west Queensland

Abstract: We describe effects of a range of fallow and crop management practices on soil properties and crop growth in wheat and grain sorghum on a red-brown earth in south-west Queensland. Results from the first 4 years of the experiment, which commenced in 1983, have been published. This paper reports results from the next 6 years. No tillage (NT) and reduced tillage (RT), combined with stubble retention, resulted in better soil-water storage during fallow but less soil nitrate-nitrogen (N) at sowing than observed wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(15 citation statements)
references
References 0 publications
0
15
0
Order By: Relevance
“…Dalal (1989) showed that stubble retention and no-tillage reduced both ESP and salt levels in a black Vertosol (Table 3). Similar effects of these practices have been observed on a red-brown earth soil (red Chromosol) in southern Queensland (Thomas et al 1995) and in long-term zero-tillage trials on grey and black Vertosols of northwest NSW (W. Felton, pers. comm.…”
Section: Cultural Practicesmentioning
confidence: 55%
See 1 more Smart Citation
“…Dalal (1989) showed that stubble retention and no-tillage reduced both ESP and salt levels in a black Vertosol (Table 3). Similar effects of these practices have been observed on a red-brown earth soil (red Chromosol) in southern Queensland (Thomas et al 1995) and in long-term zero-tillage trials on grey and black Vertosols of northwest NSW (W. Felton, pers. comm.…”
Section: Cultural Practicesmentioning
confidence: 55%
“…5). Highly mobile ions, such as NO 3 -, have been shown to concentrate deeper within the soil profile (Thomas et al 1995;Turpin et al 1998) concentration of NH 4 + has also been reported between soil depths of 1.2 and 3 m; however, in some Vertosols, the source of this deposit is unknown (Page et al 2002).…”
Section: Subsoil Nutrient Deficienciesmentioning
confidence: 99%
“…Agricultural systems modelling facilitates scenario analyses by specifying different combinations of management options, and the investigation of the impact of long-term climate variability and future climate change on agricultural systems productivity and soil C dynamics. An agricultural systems model with well-tested crop and soil modules enables the exploration of the interactions among agricultural practices in regulating soil C dynamics (Thomas et al, 1995;Heenan et al, 2004;Hooker et al, 2005;Al-Kaisi et al, 2005;Wang and Dalal, 2006;Poirier et al, 2009) across space and time, which is otherwise impractical through conducting field experiment because of the large spatiotemporal variability in both climate and soils and the possible management options.…”
Section: Role Of Systems Modellingmentioning
confidence: 99%
“…Different patterns of response of gypsum have been reported on growth and yield of different crops. Gypsum treatment to the soil is reported to increase yield of low bush blueberry (Sanderson et al, 1996), wheat and sorghum (Thomas et al, 1995) and corn and alfa-alfa (Toma et al, 1999). However, Viator et al (2002) could not obtain any response of gypsum on yield and root growth in sugarcane and described that short duration…”
Section: Discussionmentioning
confidence: 99%